PERANCANGAN FASILITAS KERJA PROSES PENGELASAN YANG ERGONOMIS (Studi Kasus pada Bengkel PT Aji Batara Perkasa) - Ronny Tuhumena; Rudy Soenoko; Slamet Wahyudi (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2014)
There are many small industryy that manufacture parts and accessories two-wheeled. Production process of parts and accessories has been done in the welding process. Welding is a common method used to connect the metal permanently. The results of observation on welding process identify there are many problems faced by operators of welding process. Welding facilities are not ergonomic and resulted in complaints of the welding operator. Results of nbm questionnaire given to operators welding showed that there are many complaints from operators. To solve the problems, this paper propose repairing on a working position and design work facilities that match with the anthropometry operators and then propose the additional aids ( jigs and a fixture ) for operators.